2021
DOI: 10.46925//rdluz.32.29
|View full text |Cite
|
Sign up to set email alerts
|

The issue of the information technology and technical terminology translatability from English into Russian: the typology and the nominative density levels

Abstract: The 21st century is characterized by its rapid scientific and technological advancement. Digital and technical inventions have resulted in computer globalization which caused the necessity of adequate translation of different kinds of English-language technical documentation, manuals, software products, etc. The article deals with the recent tendencies in translation and interpretation studies showing increasing interest to the ways English scientific and technical texts are rendered into Russian. The article … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 10 publications
0
0
0
Order By: Relevance
“…The evaluation can be started from the points of equivalence as the concern of translation by seeing their techniques of translation (Kushlyk & Smienova, 2022). The properly chosen technique of translation could guarantee a successful communication but the nonequivalent vocabulary can be a serious challenge in communication (Bobrova et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The evaluation can be started from the points of equivalence as the concern of translation by seeing their techniques of translation (Kushlyk & Smienova, 2022). The properly chosen technique of translation could guarantee a successful communication but the nonequivalent vocabulary can be a serious challenge in communication (Bobrova et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Another research concern on students' competence is also found out. It analyzes the translation competence of BA and MA students in different aspects, that is by translating without and with the help of a translation machine (Bobrova et al, 2021;Taghizadeh & Azizi, 2017).…”
Section: Introductionmentioning
confidence: 99%